2014
DOI: 10.1007/s11099-014-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of young and expanded lettuce leaves to fungicide Mancozeb: chlorophyll fluorescence, lipid peroxidation, pigments and proline content

Abstract: This work aimed to study the effects of commercial doses of the fungicide, Mancozeb, on the photosynthetic apparatus of lettuce young leaves (YL) and expanded leaves (EL). Seven days after Mancozeb application, chlorophyll a fluorescence, pigment contents, lipid peroxidation, and proline content were evaluated. Independently of leaf age, Mancozeb treatment reduced the efficiency of photosystem II photochemistry, increased the nonphotochemical quenching and proline content, decreased pigment contents, and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Other researchers compare LP status between younger and older leaves of the same plant that is upper and lower leaves, respectively. Their findings usually suggest increased LP at the lower (older) leaves (Wang et al, 2012) although it has been reported the opposite result too (Dias et al, 2014). On the other hand, root LP seems to be unaffected during ageing of the pant (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Other researchers compare LP status between younger and older leaves of the same plant that is upper and lower leaves, respectively. Their findings usually suggest increased LP at the lower (older) leaves (Wang et al, 2012) although it has been reported the opposite result too (Dias et al, 2014). On the other hand, root LP seems to be unaffected during ageing of the pant (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The crop productivity and yield as demonstrated by biomass production and plant growth rates are strongly related to the intensity of photosynthesis processes. On the contrary to the numerous experimental data on the relevant physiological and metabolic effects developed in plants cultivated under control of diverse contact fungicides (Garcia et al 2003 ; Xiao et al 2006 ; Petit et al 2008 ), impact of dithiocarbamates on the photosynthesis has not been extensively examined so far (Sau-Man Po and Ho 1997 ; Dias et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These pigments are inhibited in the presence of stress, thus altering the photosynthesis of plants [29]. However, when exposed to mancozeb, Chl and carotenoid contents decreased in let- tuce leaves, which in turn caused the pigment-protein complexes of the photosynthetic apparatus to be less stable, and photosynthetic pigments degraded more easily upon pesticide exposure [30]. Moreover, insecticides might inhibit the biosynthesis of chlorophyll by slowing down or stopping synthesis of enzymes responsible for the synthesis of photosynthetic pigments [31].…”
Section: Resultsmentioning
confidence: 99%
“…Proline content is an essential indicator in that it follows an increasing path in plants exposed to various stress factors [39]. Increases of proline content were also observed after being exposed to various pesticide stresses [30]. Proline is a non-enzymatic antioxidant that plays a protective role in membrane structure of living cells of plants exposed to various stress [40].…”
Section: Resultsmentioning
confidence: 99%